National Security Strategy of the United States, 1994-1995 : Engagement and Enlargement - Clinton, William J. (Washington Brassey's, 1995)
The White House's forecast of US defence posture outlines America's national goals and interest, world trends, regional challenges and political, economic and defence agendas
Keywords: Military readiness -- National security -- United States